2017
DOI: 10.1097/pcc.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Long-Term Central Venous Catheters Versus Transhepatic Venous Catheters in Infants and Young Children

Abstract: Without compromising future central venous access sites, transhepatic venous lines had superior duration of service without increased thrombosis, thrombolytic use, or insertion site complications relative to central venous lines. Transhepatic venous catheters had a higher infection rate, and further investigation into the etiology is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Comparisons between umbilical catheters, PICCs, tunneled CVADs, and nontunneled CVADs based on dwell time, occlusion, thrombosis, and infection risk were the primary focus of the included studies. 15,31,35,88 Generally, short-term peripheral and nonperipheral compatible therapy delivered via umbilical catheters in infants can be used. 66 PICCs were recommended for patients with congenital cardiac conditions requiring $7 days of IV therapy.…”
Section: Congenital Cardiac Conditionsmentioning
confidence: 99%
“…Comparisons between umbilical catheters, PICCs, tunneled CVADs, and nontunneled CVADs based on dwell time, occlusion, thrombosis, and infection risk were the primary focus of the included studies. 15,31,35,88 Generally, short-term peripheral and nonperipheral compatible therapy delivered via umbilical catheters in infants can be used. 66 PICCs were recommended for patients with congenital cardiac conditions requiring $7 days of IV therapy.…”
Section: Congenital Cardiac Conditionsmentioning
confidence: 99%
“…The feasibility of these alternative routes of access have been previously reported in patients with congenital heart disease. Utilization of transhepatic catheters may be associated with increased rates of complications, such as thrombus formation, catheter dislodgement, and infection, in comparison to traditional catheter routes; however, no long-term complications or increase in infection-related catheter removal have been found [13][14][15][16][17]. Thus, consideration of these alternative access devices and approaches should be considered, though reserved for children with limited availability of other sites [2].…”
Section: Discussionmentioning
confidence: 99%
“…Utilisation of trans-hepatic catheters may be associated with increased rates of complications, such as thrombus formation, catheter dislodgement, and infection, in comparison to traditional catheter routes; however, no long-term complications or increase in infectionrelated catheter removal have been found. [14][15][16][17][18] Thus, consideration of these alternative access devices and approaches should be considered, though reserved for children with limited availability of other sites. 2 Vessel visualisation with ultrasound should be employed whenever achievable to minimise vessel trauma and the number of access attempts.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the transhepatic venous lines had superior duration of service without increased thrombosis, thrombolytic use, or insertion site complications relative to central venous lines despite a higher infection rate. 49…”
Section: Access Through Unusual Veinsmentioning
confidence: 99%